The association of serum gamma-glutamyl transpeptidase level and other laboratory parameters with blood pressure in hypertensive patients under ambulatory blood pressure monitoring - Ortakoyluoglu A; Boz B; Dizdar OS; Avcı D; Cetinkaya A; Baspınar O (Dove Medical Press, 2016)
Adile Ortakoyluoglu, Betul Boz, Oguzhan Sitki Dizdar, Deniz Avci, Ali Cetinkaya, Osman Baspinar Department of Internal Medicine, Kayseri Training and Research Hospital, Kayseri, Turkey Background: Hypertension is a very important cause of morbidity and mortality. Serum gamma-glutamyl transpeptidase (GGT) is a biomarker of oxidative stress and associated with increased risk of hypertension and diabetes. The aim of this study was to evaluate the association of serum GGT level, which is an early marker of inflammation and endothelial dysfunction, with the deterioration of the diurnal rhythm of the blood pressure.Methods: A total of 171 patients with hypertension were included in this study. Patients whose nighttime mean blood pressure, measured via ambulatory blood pressure monitoring, decreased between 10% and 20% compared with the daytime mean blood pressure were defined as “dippers”, whereas patients with a nighttime blood pressure decrease lower than 10% were defined as “non-dippers”.Results: A total of 99 hypertensive patients (65 females/34 males) were classified as dippers and 72 patients (48 females/24 males) as non-dippers. The mean age of the non-dipper group was significantly greater than the dipper group. Serum GGT, C-reactive protein and uric acid levels were significantly higher among patients in the non-dipper group. Negative correlations were detected between GGT levels and diurnal systolic and diastolic blood pressure decreases.Conclusion: Our findings revealed that GGT level was higher in the non-dipper group, and was negatively correlated with the nighttime decrease of diurnal blood pressure. C-reactive protein and uric acid levels were also higher in the non-dipper group. However, future randomized controlled prospective studies with larger patient populations are necessary to confirm our findings. Keywords: gamma-glutamyl transpeptidase, hypertension, ambulatory blood pressure monitoring, laboratory parameters